1993
DOI: 10.1128/jb.175.7.1891-1899.1993
|View full text |Cite
|
Sign up to set email alerts
|

Organization of a Clostridium thermocellum gene cluster encoding the cellulosomal scaffolding protein CipA and a protein possibly involved in attachment of the cellulosome to the cell surface

Abstract: The nucleotide sequence was determined for a 9.4-kb region of Clostridium thermocellum DNA extending from the 3' end of the gene (now termed cipA), encoding the S1/SL component of the cellulosome. Three open reading frames (ORFs) belonging to two operons were detected. They encoded polypeptides of 1,664, 688, and 447 residues, termed ORF1p, ORF2p, and ORF3p, respectively. The COOH-terminal regions of the three polypeptides were highly similar and contained three reiterated segments of 60 to 70 residues each. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
115
0
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(119 citation statements)
references
References 30 publications
2
115
0
2
Order By: Relevance
“…Protein OlpA has been localized to the cell surface of C. thermocellum (286). It was hypothesized that this region may anchor the cellulosome to the cell surface (87). However, there was no binding found between the dockerin of CipA and the receptor domain of OlpA (287).…”
Section: Attachment Of Cellulosomes To the Cell Surfacementioning
confidence: 89%
See 1 more Smart Citation
“…Protein OlpA has been localized to the cell surface of C. thermocellum (286). It was hypothesized that this region may anchor the cellulosome to the cell surface (87). However, there was no binding found between the dockerin of CipA and the receptor domain of OlpA (287).…”
Section: Attachment Of Cellulosomes To the Cell Surfacementioning
confidence: 89%
“…These four genes form two operons (87). All three ORFs encode C-terminal domains (three repeats of about 65 amino acid residues) responsible for the cell surface layer (S-layer) location of the encoded proteins.…”
Section: Attachment Of Cellulosomes To the Cell Surfacementioning
confidence: 99%
“…These studies suggest that, in general, S-layer proteins have two functional regions: a cell-wall-targeting domain, which in most of the organisms investigated thus far is located at the N-terminus, and a C-terminal self-assembly domain. The existence of a cell-wall-targeting domain in S-layer proteins was substantiated by Fujino et al (1993) and Lupas et al (1994), who identified motifs of approximately 55 amino acids, containing 10-15 conserved residues, which were designated SLH (S-layer homology) domains. SLH domains, usually composed of one to three modules, are frequently used means for targeting proteins to the cell surface.…”
Section: Interactions Of Scwps and S-layers From Bacillaceaementioning
confidence: 91%
“…These particular sequences are thought to be characteristic of enzymes integrated into the cellulosome structure [4], and yet they are observed with cellulolytic systems of Clostridium thermocellum [4, 51 and Clostridium cellulovorans [6]. These organisms secrete highmolecular-mass particles named cellulosomes which are active against cellulose, and they possess an assembly factor, CbpA in C. cellulovorans [7] and CipA in C. thermocellum [8, 91. Four genes, celCCA, celCCC, coding for enzymes of the cellulolytic system of C. cellulolyticum have been completely sequenced and the four corresponding proteins are members of three different fami-…”
mentioning
confidence: 99%